ANALISIS KEPUASAN WISATAWAN PENGGUNA JASA TRANSPORTASI KOPERASI ANGKUTAN PARIWISATA SURYA KENCANA SANUR - Ayu Trisna Dewi, Ni Komang; Suwena, I Ketut; Sudana, I Putu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 6 No 2 (2018): Jurnal IPTA (December 2018)DO - 10.24843/IPTA.2018.v06.i02.p03, 2018)
The aim of this research is to determine tourists’ tourist satisfaction analysis of users of tourism transport cooperative services Surya Kencana Sanur. Data was collected using observation method, interview, questionnire, documentation, and literature study. Respondents were determined using purpose sampling method with 18 indicators, and total respondents involved were 108 individuals. Data were analyzed using quantitative descriptive analysis technique with Importance Performance Analysis (IPA) with Likert scale to determine each indicator’s quadrant. Services dimension studied were tangibility, reliability, responsiveness, assurance, and empathy. He results of this research showed that the average of tangibility variable is 88,60% categorized as less satisfied, average of reliability variable is 92,84% categorized as highly satisfied, average of responsiveness variable is 89.13% categorized as less satisfied, average of assurance variable is 89.70% categorized as less satisfied, and average of empathy variable is 89.39% categorized as less satisfied. Overall total of appropriate level is 89.77%. From this research, it is expected that the company improves services which are considered as important by tourists, but drivers’ performances have not met tourists’ expectation. Indicators which have fulfilled tourists’ expectation need to be maintained.